Petani Durian dalam Masyarakat Risiko - Muhamad Raihan Firdaus; Sayyidah Lailatus Sonia; Kadita Syarifatul Aulia (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Indonesia is a country that has an agrarian title, because of its vast and fertile land area, so that most Indonesian people make a living as farmers. There are also several types of farmers, one of which is a profit-oriented commercial farmer and durian farmers are one of the commercial farmers. This research will focus on durian farmers in risk communities. The research point was conducted by researchers in Pakis Village, Panti District, Jember Regency, East Java. The purpose of this study is to find out how the forms of risk faced by durian farmers and also how they respond or adapt to these risks. The research method used by researchers is a qualitative method with a phenomenological approach. The results of research conducted by researchers are knowing that 1) Durian farmers are victims of ecological risks that occur globally 2) Farmers are more inclined to choose to rent at Perhutani 3) Using an intercropping system to minimize the risks they will face later 4) Selection of plants durian, banana, and coffee as a choice of plants to be planted.